Family contact in foster care in Portugal. The views of children in foster care and other key actors - Delgado, Paulo (2018)
This is a pilot study on the sensitive issue of how children and young people experience family contact in foster care, and the views of key adults in their lives on the same issue. There is a special focus on the children's experiences, opinions, and feelings. The study is a response to the relative scarcity of literature on family contact based on the experiences of children and adults in caring roles. This is a qualitative and exploratory study, with a sample of 10 children and young people in care in the district of Porto, aiming to identify key issues and areas for further examination. The results allow us to conclude that the possibility of maintaining contact is positively evaluated. However, perspectives on the relationships involved, and on the reactions to and difficulties associated with visits, revealed considerable disagreement among the actors. A possible set of implications drawn from the findings pointed out to the importance of developing a monitored cooperation that improves communication processes in order to take into account the children's and young people's views in the decision‐making process; and to develop more attentive and open working relationships with parents throughout the foster care placement.